Rimba Lestari unique green treasure on campus - Mimi Rabita, Abdul Wahit (2021)
PEKAN, 12 March 2021 - Universities as knowledge leaders play an important role in implementing sustainable development education among university residents and the community in line with the Sustainable Development Goals (SDGs) to be achieved by 2030.